Virtual Learning Environment as a Strategy to Strengthen Reading Comprehension in Basic Secondary Education Students - Murillo , Hernán Javier Guzmán; Ortega, José Marcelo Torres; Buelvas, León Julio Arango (Journal of Ecohumanism, 2024)
This article presents the results of a research study aimed at strengthening reading comprehension in secondary school students through the design and implementation of a virtual learning environment (VLE). The study was conducted using a mixed-methods approach, integrating qualitative and quantitative methodologies to assess the impact of the VLE on students’ reading skills. Using interactive tools and collaborative activities, the virtual environment facilitated the development of critical competencies such as identifying main ideas, making inferences, and interpreting texts. The research was carried out with a sample of ninth-grade students from an educational institution in Montería, Colombia, selected through purposive sampling. The results showed significant improvements in students’ reading comprehension, highlighting the role of the VLE as an effective pedagogical tool for promoting meaningful learning in diverse educational contexts. This study emphasizes the importance of integrating digital technologies into teaching and learning processes to strengthen reading competencies in secondary education.